HUBUNGAN PEKERJAAN DENGAN KEAKTIFAN IBU DATANG KE POSYANDU GELANG DAN KROYO DESA GELANG KULON KECAMATAN SAMPUNG KABUPATEN PONOROGO. - Sumini Sumini; Vera Puspita Anggraini (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Activeness is a person's mental and emotional Involvement for achieving goals and takingresponsibility in them. Based on the Register of Weighted Weight Cohort Coordinator as an initialproblem on November 9, 2016 at integrated health post Gelang and Kroyo on 100 mother toddlersabout visit integrated health post, 30 people (30%) were active to integrated health post and 70(70%) were inactive to integrated health post. A preliminary study of 10 mother-to-toddlers throughinterviews obtained 3 people (3%) active and 7 people (7%) were inactive. This is because ofbusyness as Teachers, Nurses, Farmers and Traders. While the mother is active as an IRT. Thisresearch is raining to know the relation of mother work with mother activity to come to integratedhealth post.This type of research is cuantitative with correlational approach and research design withretrospective form. Population in this study were as many as 100 mothers children in integratedhealth post Gelang and Kroyo, with a sample of 80 mother children by using random sampling technique. The study was conducted 12-04-2017. Were one independent variable (work mother of atoddler) and one dependent variable (liveliness of mother come to integrated health post). Thisresearch was Book Register Cohort. Data were analyzed using statistical test by using paired Chi-Square Test, level was determined by the value < 0,05.The results of the research showed that most of mother’s work are 61 people (76,25%), AndMost of under mother children are not as active as 60 people (75%). From the results of calculationsperformed using Chi-Square Test showed that there is a relationship of work with the liveliness of themother came to integrated health post in intregated healt post Gelang n Kroyo level with significancelevel 0,000 < 0,05 and r : 0,695 mean strong relationship.This research was hope midwife to make do counseling about the importance of comingchildren to integrated health post and increasing the coverage of D/S in Integrated health postGelang and Kroyo.Midwives are expected to actively to mobilize the people, especially mothertoddlers to keep coming to weigh their children.